The Effect of Powtoon Animation Media towards Motivation and Learning Outcomes of Student on Chemical Equilibrium Material - Nursina Sya'bania; Apriani Megati; Germanus Gleko; Falentinus Pio; Febriyanti (Sean Institute, 2022)
The research was a quasi-experiment that aimed to determine the effect of powtoon animation media toward motivation and learning outcomes of student on chemical equilibrium. This research uses guided inquiry learning model in the teaching process. The independent variable in this research was powtoon animation media in guided inquiry learning model and the dependent variable was motivation and learning outcomes at class XI Exact SMAN 2 Maumere. The population of this research were all of class XI Exact SMAN 2 Maumere consist of 4 class and totaling 123 students. The sample consisted of two classes of class XI Exact 4 as an experiment with 23 students and class XI Exact 2 as the control with 20 students. Data collection technique was obtained from questionnaires for motivation and objective test which consist of 20 items multiple choice. The average of learning motivation in experiment class is higher than control class with scores of 81.33 and 71.41. The average of learning outcomes in experiment class was high 81,7 than control class was 74,5. The data analysis technique used descriptive statistical analysis and inferential statistical analysis for learning outcomes. The hypothesis test using t test shows that tcalculate (1,90) > ttable (0,60) on ═ 0,05. Based on the results of data analysis can be concluded that there was an effect of powtoon animation media toward motivation and learning outcomes on Chemical Equilibrium Material.